Alona kotovi sp. nov., a new species of Aloninae (Cladocera: Anomopoda: Chydoridae) from South Vietnam - Sinev, Artem Y. (Zootaxa, 2012)
A new species of anomopod related to Alona quadrangularis (Cladocera: Anomopoda: Chydoridae) is described fromstreams in South Vietnam. Alona kotovi sp. nov. differs from the other species of Alona s. str. (the quadrangularis-group)by the morphology of its postabdomen, labrum and thoracic limbs. The presence of a short spine at the end of the malepostabdominal claw is unique to the new species. A. kotovi sp. nov. is well-distinguished from two other Old Worldspecies, A. quadrangularis and A. kolwezii, yet shares numerous similarities with South American A. yara. This is one more case of connection between South American and Australasian faunas of Chydoridae.